Radiating therapy in patients with a cardiac pacemaker or cardioverter Part I. The structure and mechanism of cardiac pacemakers - Ziółkowska, Ewa; Wiśniewski, Tomasz; Zarzycka, Małgorzata; Meller, Aleksandra; Woźniak-Wiśniewska, Anita (Contemporary Oncology/Współczesna Onkologia, 2008)
With an aging population and the increased use of pacemakers (ICPs) and implantable cardioverter-defibrillators (ICDs), the incidence of patients presenting for radiation therapy with a pacemaker or ICD is increasing. ICDs are pacemakers that are also able to deliver a high voltage shock in case of a life-threatening ventricular tachycardia or ventricular fibrillation. The usual indication for placement of an ICP is the presentation of bradycardia and its resultant symptoms of syncope, semi-syncope or atrioventricular block. Therapeutic irradiation may cause pacemakers to malfunction due to the effects of ionizing radiation or electromagnetic interference. Modern pacemakers, using complementary metal oxide semiconductor (CMOS) circuitry, are more sensitive than older bipolar semiconductor devices. Precautions are necessary to minimize the risk to patients with ICP and ICD devices during radiotherapy. The aim of the study is to introduce oncologists to the construction and operation of pacemakers and performance conditions of the safe use of ionizing radiation in oncological patients with pacemakers during radiation therapy.